2012
DOI: 10.1177/0261927x12438538
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Communicate in English Among Iranian Non–English Major University Students

Abstract: The purpose of the present study is to examine willingness to communicate in the second language (L2WTC) construct and its underlying variables among non–English major students in Iran. The study used WTC and socioeducational models for examining L2 communication and L2 learning. Descriptive statistics, Pearson correlation, and t test were used with a sample of 158 non–English major university students. An L2 communication model was also proposed and tested using structural equation modeling. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
104
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(127 citation statements)
references
References 17 publications
19
104
4
Order By: Relevance
“…As such, Ghonsooly et al (2012), investigated WTC among Iranian non-English major university students. His research participants were chosen among students of humanities (Arabic language and literature, social sciences, and geography) and Engineering students (computer, electronic, mechanic, industrial, and chemistry engineering).…”
Section: Willingness To Communicatementioning
confidence: 99%
See 1 more Smart Citation
“…As such, Ghonsooly et al (2012), investigated WTC among Iranian non-English major university students. His research participants were chosen among students of humanities (Arabic language and literature, social sciences, and geography) and Engineering students (computer, electronic, mechanic, industrial, and chemistry engineering).…”
Section: Willingness To Communicatementioning
confidence: 99%
“…Results revealed the positive relationship between perceived communicative competence and WTC and negative relationship between perceived communicative competence and anxiety. Ghonsooly et al (2012), following Clément (1980Clément ( , 1986, considered L2 self-confidence as anxiety and perceived communicative competence. His study showed that as anxiety decreases perceived communicative competence increases, and WTC increases too.…”
mentioning
confidence: 99%
“…The extension of WTC studies to Iranian learners widens the range of cultural contexts in which this construct has been applied. Although studies of the WTC of Iranians in Iran have taken place (e.g., Ghonsooly et al, 2012), no reports have been published so far specifically targeting this group in other countries. As a result of past political events in Iran leading to migration, and an increasing number of Iranian Study Abroad students in overseas universities, this nationality group makes up a significant component of many English language classes.…”
Section: Context and Wtcmentioning
confidence: 99%
“…1). emphasise the role that self-confidence plays in WTC, as do Alemi et al (2011) andGhonsooly et al (2012) in regard to the Iranian context. In contrast, Farnaz described her English learning experiences in her Iranian high school as motivating, but that she lacked confidence in speaking (Int.…”
Section: The Learners' Wtc In Nz Esl Classrooms In Comparison To Theimentioning
confidence: 99%
See 1 more Smart Citation